2015
DOI: 10.1016/j.devcel.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Integrin Adhesions Form on All Matrix Rigidities after Integrin Activation

Abstract: Integrin adhesions assemble and mature in response to ligand binding and mechanical factors, but the molecular-level organization is not known. We report that ∼100-nm clusters of ∼50 β3-activated integrins form very early adhesions under a wide variety of conditions on RGD surfaces. These adhesions form similarly on fluid and rigid substrates, but most adhesions are transient on rigid substrates. Without talin or actin polymerization, few early adhesions form, but expression of either the talin head or rod dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
212
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(237 citation statements)
references
References 40 publications
15
212
1
Order By: Relevance
“…At the microscale, alginate concentrations below 3% (w/v) will produce gels with moduli as low as HH 28 tendon. However, we chose to focus on the effects of nanoscale moduli on TPC responses because integrins that mediate cell-matrix interactions are nanoscale in dimension (Changede et al, 2015; Nermut et al, 1988). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the microscale, alginate concentrations below 3% (w/v) will produce gels with moduli as low as HH 28 tendon. However, we chose to focus on the effects of nanoscale moduli on TPC responses because integrins that mediate cell-matrix interactions are nanoscale in dimension (Changede et al, 2015; Nermut et al, 1988). …”
Section: Resultsmentioning
confidence: 99%
“…Considering integrins are nanoscale in dimension (Changede et al, 2015; Chen and Singer, 1982; Erb et al, 1997; Franz and Muller, 2005; Kanchanawong et al, 2010), we examined TPC responses to different nanoscale elastic moduli. RGD-alg gels differentially regulated tendon marker expression as a function of embryonic stage-specific nanoscale modulus after 7 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“…A C-terminal fragment of talin from IBS2 to ABS3 rescues the proliferation defects in epithelial cells lacking talin (Wang et al, 2011), and the IBS2 region is needed for talin to form the initial clusters of ∼50 integrins in nascent adhesions (Changede et al, 2015). For talin interactions alone to be sufficient to generate integrin clusters larger than four integrins, one integrin might need to be able to bind to more than one talin molecule, thus forming a network of integrins that are separated by the distance between the two IBSs in the talin molecule or dimer (Fig.…”
Section: Box 2 Testing the Importance Of Inside-out Integrin Activatmentioning
confidence: 99%
“…Zervas et al, 2011), and thirdly, how integrins adopt a regular spacing within adhesions (Rossier et al, 2012). However, fragments of the head or rod domains can function in place of talin in forming nascent adhesion clusters (Changede et al, 2015), suggesting that single IBSs can function with other IAPs in generating this matrix.…”
Section: Box 2 Testing the Importance Of Inside-out Integrin Activatmentioning
confidence: 99%
“…Sheetz et al show that cell adhesions are loose aggregates of integrin clusters. These tight clusters of integrins each have a size of ~100 nm, and is each composed of ~20–50 molecules [131]. Interestingly, it has been concluded that clustered, but not individually distributed, plasma membrane proteins ( e.g.…”
Section: Cellular Mechanosensing Of Matrix Rigiditymentioning
confidence: 99%